Teknologi Informasi dan Komunikasi (TIK) dalam Peningkatan Mutu Administrasi Pendidikan di Temanggung - Sholeh Kurniandini; ZaidatulArifah; Ahmad Zakariya (STAI Terpadu Yogyakarta, 2022)
Information and communication technology is very influential in improving the quality of education administration to carry out tasks in accordance with the vision, mission and goals of the school. The importance of technology in improving the quality of education administration will affect the quality and quality of schools. The research method uses field research. Sources of data obtained through information and communication with SMA Negeri 1 Temanggung. The results of the study are 1) Through the process of developing information and communication technology at SMA N 1 Temanggung, it has developed and made a significant contribution. 2) The urgency of information and communication technology plays a role in improving the quality of education.